Entangled exclusions: Borders, frontiers and urban geopolitics from northeast India - DAS, Prerona (Institutional Knowledge at Singapore Management University, 2024)
An epicentre of ethnicity-based identity politics and exclusions, India's northeastern region has long been politically imagined as both a ‘frontier’ and ‘borderland’ for state control, territorialization, extractive economies and (re)developments by colonial and subsequent post-colonial regimes. In post-independence India, the region experienced many territorial assertions made on ethnic grounds. With the rise of religio-national and neoliberal politics, new urban ‘developments’ and connectivity projects in the region have deepened exclusions based on class, caste, ethnic and religious borders. These have, in turn, led to further displacement, enclavization, and ghettoization of minority communities who are deemed ‘non-native’ along ethnocentric lines. Taking two cases from Shillong and Guwahati, we introduce the concept of entangled exclusions to analyse the layered, intertwined, multi-scalar nature of divides within these frontier cities. We argue these cities are critical sites for understanding urban geopolitics where concentrated entanglements of exclusions and (re)borderings become manifest as these cities experience new infrastructural investments.